CREATIVE AND INNOVATIVE AUDIOVISUAL-BASED LEARNING METHODS TO ENHANCE CONCENTRATION AND DISCIPLINE IN FIQH - Albetrik Mezontara; Asiyah; Nasron (El Midad, 2025)
This study is motivated by the lack of student concentration and discipline during the learning process. The research aims to: 1) identify the basic considerations of teachers in implementing creative and innovative learning methods in Fiqh subjects at MI Terpadu Mutiara Assyifa, Bengkulu City; 2) explore how these methods are applied to foster concentration and discipline; 3) examine the supporting and inhibiting factors in the use of audiovisual-based learning methods to enhance concentration and discipline; and 4) evaluate the implementation of these methods. This study employs a descriptive qualitative approach, using data collection techniques such as interviews, observation, and documentation. Data were analyzed through the processes of data reduction, data display, and conclusion drawing. The findings reveal that: 1) teachers consider the learning material, student characteristics, time allocation, and learning objectives when selecting teaching methods; 2) methods such as lectures, question-and-answer sessions, repetition, and praise help improve student concentration; 3) discipline is developed through habituation, role modeling, rewards, and punishments; and 4) supporting factors include teacher competence, availability of facilities, and student motivation, while inhibiting factors include inadequate infrastructure and limited resources. This study highlights the importance of integrating audiovisual media into innovative learning strategies to enhance both cognitive engagement and character development, particularly in Fiqh education